Public Spaces Transformations in Latin America during Covid19. Community resilience and Tactical Urbanism in Bogota, Quito and Mexico City - Marino Zamudio, Raul; Nys, Maud; Vargas, Elkin; Riveros, Alejandra (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2025)
The public space access restrictions and confinement measures due to the Covid19 pandemic caused important transformations in the use of living spaces and public space. The research presented here investigated the impact of those restrictions in the community, using an online survey deployed at the time of the lockdown worldwide (March-December 2021), collecting important information about the challenges and adaptation of housing and public spaces in Bogota, Quito and Mexico DF. Following on the topic, the project: Recreating Cultures: Heritage, memory and place as a base to strengthen social fabric in Tunal, Bogota¨, was aimed to strengthen social fabric and public spaces using heritage, memory and local art initiatives. This research was aimed to understand the adaptations/transformations of public spaces to the Covid19 phenomenon and access to public spaces, streets, parks and other urban spaces, and the importance of tactics such as tactical urbanism to revalue public spaces in health crisis times such as tactical urbanism and placemaking. Therefore, the lessons learned from the Covid19 pandemic will leave an imprint on the meaning and value of community and neighbourhood and suggest that political action on the territory must move towards community participation and community engagement. The revaluation of public space through participation, tactical urbanism and citizen activism can influence local governments so that urban agendas with sustainability approaches have a much faster implementation and concepts such as community engagement, security, walkability, accessibility and inclusion become priority actions for the recovery of public spaces and communities.